Identifikasi Environment Critical Index (Indeks Kekritisan Lingkungan) Menggunakan NDVI dan LST di Kota Surabaya - Agusman, Ridho; Mataburu, Ilham Badaruddin (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
The decline in environmental quality, which can lead to an increase in air temperature, is an adverse impact of the phenomenon of urbanization and industry. An area will be more comfortable to live in if it is more densely vegetated. The capital of East Java province is Surabaya, the second largest city in Indonesia. ECI was analyzed based on LST and NDVI algorithms. Observations of surface temperature and vegetation density in Surabaya City were conducted in 2013 and 2023 by utilizing Landsat-8 OLI satellite images. NDVI classification levels are divided into 4, namely non-vegetation, low vegetation, medium vegetation, and high vegetation. Low vegetation is the most dominating NDVI level in 2013 and 2023 with 80.6% and 84.9% respectively. Surface Temperature Level in Surabaya City has increased in both maximum and minimum temperatures over the last 11 years. It can be seen that the temperature distribution with a level of >36 degrees Celsius in 2023 experienced a very significant increase, reaching 75.6%. The Environmental Critical Index in Surabaya City has four classifications, namely non-critical, low, medium, high. Each level of environmental criticality in Surabaya City was analyzed based on LST and NDVI within 11 years, namely 2013 and 2023. The level of environmental criticality in Surabaya City has generally decreased due to the increase in vegetation area, although the level of decrease has not been significant. Keyword: NDVI, LST, ECI